Nasal Carriage of Methicillin Resistant Staphylococcus Aureus among Medical Personnel of Salah Al-Din Hospitals using Classical Method and PCR Technique - Nihad Abdul-Hussain Jafar (Journal of Global Pharma Technology, 2016)
Objectives: To screen medical personnel of four hospitals at Salah Al-Din governorate for MRSA, and to compare between the classical method and PCR method for detection of Staphylococcus aureus and MRSA. Materials and Methods: A total of 279 nasal swabs were taken from medical personnel of four hospitals in Salah al-Din (Salah Al-Din General Hospital, Tikrit Teaching Hospital, Samarra General Hospital and Baiji General Hospital). Staphylococcus aureus isolates diagnosed by both classical methods based on morphology, coagulase test, DNase test and mannitol salt agar fermentation, and by PCR by detection of femA gene .The isolates diagnosed as MRSA using classical method by its sensitivity to Cefoxitin in disc diffusion method and by detection of mecA gene with PCR. Results: The results showed that out of the 279 swabs taken from the medical staff of four hospitals in Salah al-Din, 88 were isolated as S. aureus (31.5%) using the classical method used in the hospitals of the governorate under study, and 58 (65.9 %) of them were methicillin resistant S. aureus using the Cefoxitin antibiotic method. However, the PCR results showed that only 57 isolates (20.4%) were diagnosed as S. aureus and that the number of isolates of S. aureus that possessed the mecA gene was only 24 isolates (42.1%) from the total isolates. Conclusion: The classical methods used in most Iraqi hospitals are not accurate in diagnosing S. aureus isolates and MRSA isolates, since 31 (35.2 %) isolates of the 88 isolates were misdiagnosed as S. aureus by the classical method. Furthermore, 34 (58.6 %) isolates of S. aureus were misdiagnosed as MRSA by the classical disc diffusion method.Keywords: MSRA, Nasal carriage, Meca.